Patterns of Posttraumatic Stress Disorder Symptoms and Posttraumatic Growth in an Epidemiological Sample of Chinese Earthquake Survivors: A Latent Profile Analysis - Cao, Chengqi; Wang, Li; Wu, Jianhui; Li, Gen; Fang, Ruojiao; Cao, Xing; Liu, Ping; Luo, Shu; Hall, Brian J.; Elhai, Jon D. (Frontiers in Psychology, 2018)
Background: Posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG) are different psychological outcomes triggered by exposure to extraordinarily traumatic events. In this study, we aimed to examine patterns of co-occurrence between DSM-5 PTSD symptoms and PTG, among natural disaster survivors, and to clarify whether empirically-based subgroups differed by several specific predictors. Methods: Latent profile analysis was used to examine patterns of self-reported PTSD symptoms and PTG in an epidemiological sample of 1063 Chinese earthquake survivors. Results: Three distinct profiles were identified, involving high PTSD/high PTG, mild PTSD/mild PTG, and mild PTSD/high PTG. Class membership was predicted by several variables, especially different sources of perceived social support. Conclusion: Our findings contribute to the knowledge about the coexisting patterns of PTSD and PTG, and provide suggestions for identifying high-risk individuals and providing effective interventions in clinical practice.